ANALISIS PENGARUH NON PERFORMING LOAN (NPL) TERHADAP RETURN ON EQUITY PADA KOPERASI WANITA (KOPWAN) KARTIKA SARI KOTA BIMA - wahdatunjannah, wahdatunjannah; Rimawan, M. (Perpustakaan dan Penerbitan Unismuh Makassar, 2019)
This purpose of this research to know and analyze the effect of Non Performing Loan (NPL) to Return On Equity (ROE) on Koperasi Wanita (KOPWAN) Kartika Sari in Bima Town. The pupulation used is financial statement data which consists of working paper data, balanced sheets, and calculation of operating result for 23 years and researh samples for 5 years with the sampling used is purposive samping with the criteria (1) financial statement data available for 5 consecutive years according to 2014-2018 (2) the 5 years sample data already represent axisting population data for reseach needs. Data analysis techniques used are simple linear regression, simple correlation coefficient, coefficient of determination and hypothesis testing ( 2 party T test). Based on the resulth of the analysis showed that Non Performing Loan (NPL) affect the Return On Equity of Kartika Sari woman’s coorperatives in Bima town. This shows that Non Performing Loan have little effect on coorperative.